Eksplorasi Ruang Lingkup Filsafat: Logika, Estetika, Etika, Politik, dan Metafisika dalam Perspektif Pendidikan Islam - Ahmad Mudzakkir; St. Maemunah; A. Marjuni; Afifuddin Harisah; Suarni (Socratika: Journal of Progressive Education and Social Inquiry, 2025)
Philosophy serves as a crucial foundation in shaping Islamic education that focuses on the comprehensive development of human potential, encompassing intellectual, moral, social, and spiritual dimensions. This study employs a conceptual approach grounded in a literature review using descriptive-reflective analysis. The findings indicate that logic functions to cultivate students' critical and rational thinking patterns. Aesthetics contributes to fostering appreciation for beauty and harmony within the educational process. Ethics forms the basis for the development of noble character and just social behavior. Politics provides insight into justice, deliberation, and social responsibility in communal life. Metaphysics strengthens students’ transcendental dimensions by offering understanding about human nature, life purpose, and the relationship with God. Integrating philosophical domains into Islamic education encourages the emergence of a knowledgeable generation with noble character, critical thinking, creative expression, and commitment to Islamic values. With a strong philosophical foundation, Islamic education is well-positioned to respond to the challenges of globalization, technological advancement, and socio-cultural changes, while simultaneously reinforcing identity and noble values as guiding principles in life.